Malaysia : Report on the Observance of Standards and Codes (ROSC), Corporate Governance Country Assessment - World Bank (Washington, DC, 2012)
This ROSC assessment of corporate governance in Malaysia benchmarks law and practice against the OECD Principles of Corporate Governance, and focuses on listed companies. Important corporate governance reforms have been implemented in Malaysia since 1998, when a high-level Finance Committee on Corporate Governance, consisting of both government and industry, was formed to identify and address weaknesses highlighted by the Asian financial crisis. Key reforms have included the development of a comprehensive master plan to further develop the capital market, the demutualization of Bursa Malaysia, introduction of a Code of Corporate Governance, and changes in the composition and role of its Board of Directors. In 2004, disclosure rules and corporate whistleblower protections were strengthened. In 2005, major reforms commenced to overhaul government-linked corporations (GLCs). The report stresses that in order to further improve its corporate governance practices, Malaysia faces the following challenges: the government's level of equity ownership remains large; free float remains low; and directors' accountability and protection for minority shareholders need further improvement. In addition, the role of institutional investors and shareholder activism in the corporate governance framework needs to be strengthened. This report identifies several key measures that focus on enforcement and implementation, including: Continued and consistent enforcement of disclosure and reporting requirements by the Securities Commission, with a focus on quality of information provided; Implementation of legislative reform to strengthen directors' independence and accountability to investors; and Development of a legal basis for and promotion of an active institutional investor community.